STUDI KASUS PEMILIHAN HINDU SEBAGAI AGAMA MASYARAKAT TENGGER - Zakia Sukha Jamilah; Faza Dhora Nailufar (Journal of Public Power, 2021)
This paper intends to find out the reasons and backgrounds why the Tengger people chose their religion to Hinduism amid the invasion of major religions such as Islam and Christianity. In 1965, precisely after the emergence of Law No.1 / PNPS / 1965 concerning the prevention of misuse and or blasphemy of religions which were recognized by the state, people with traditional beliefs were required to choose religion they would write down on their ID card column. Most of the Tengger people choose to write "Hindu" as their religion. This election has gone through a long history, the Tengger community has received various invasions from major religions starting from the Majapahit kingdom to the present. The data collection method used was the collection of documents and literature about the Tengger community. The analysis was carried out by linking the reasons for choosing the Hindu religion with the theory of community choice. The Hindu religion was finally chosen after the Tengger community (who still believed in traditional) saw the similarity of the rituals and habits they often did. In addition, several political reasons that are sensitive to Islam and Christianity have also been the driving force for the selection of Hinduism as the religion of the majority of the Tengger community.